TAMI-45. MICROGLIAL CYTOKINES INDUCE INVASIVENESS AND PROLIFERATION THROUGH PYK2 AND FAK ACTIVATION IN HUMAN GLIOBLASTOMA CELL. (12th November 2021) - Nunez, Rebeca; Valle, Miguel Mayol-Del; Almodovar, Luis; Kucheryavykh, Lilia
Abstract: Glioblastoma (GBM) is the most aggressive and highly invasive primary brain tumor in adults. Evidence suggests that microglia create a microenvironment favoring glioma invasion and proliferation. Indeed, previous reports indicate the involvement of focal adhesion kinase (FAK) signaling cascades in glioma cell proliferation. Besides, studies from our laboratory support a critical role of Pyk2, a relative of FAK, in glioma invasion by tumor-infiltrating microglia. However, the microglial-released factors modulating Pyk2 and FAK signaling pathways are unknown. In this study, 20 human GBM specimens were evaluated to identify the cytokine expression patterns in purified microglia and FAK and Pyk2 phosphorylation in glioma cell fraction by RT-PCR and western blot. A Pierson correlation test demonstrated a high correlation (0.8-1.0) of gene expression for PDGFα, PDGFβ, SDF-1α, IL-6, IL-8, and EGF in percoll-purified microglia, and pPyk2(Y579/580) and pFAK(Y925) levels in glioma cell fraction. The role of cytokines in cell invasion and proliferation by Pyk2/FAK activation was further investigated in primary cell lines from three patients. Thirty percent up-regulation of pPyk2 and pFAK was detected in glioma cells treated (2 hrs.) with microglia conditioned media (MCM) compared to control cells. siPyk2 or siFAK knockdown identified IL-6 (100 μM) and EGF (1 μM) as key factors of Pyk2- and FAK-dependent activation in all glioma cell lines. Similar results with siPyk2 or siFAK were observed for matrix degradation, invadopodia formation, cell viability, and mitosis. Indeed, Tocilizumab (IL-6R blocker, 100 ng/mL) and Gefitinib (EGFR blocker, 1 μM) reversed the effect of MCM on glioma cell proliferation and invasion in all cell lines evaluated. These findings support a pivotal role of Pyk2 and FAK in enhancing proliferation and invasion of glioma tumors through IL-6 and EGF-dependent pathways. The latter could be of clinical relevance for new therapeutic developments in GBM patients.